2014
DOI: 10.1371/journal.pone.0109443
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Analysis Reveals Globally Differential Regulation of Human Long Non-Coding RNA and Protein-Coding Genes

Abstract: Transcriptional regulation of protein-coding genes is increasingly well-understood on a global scale, yet no comparable information exists for long non-coding RNA (lncRNA) genes, which were recently recognized to be as numerous as protein-coding genes in mammalian genomes. We performed a genome-wide comparative analysis of the promoters of human lncRNA and protein-coding genes, finding global differences in specific genetic and epigenetic features relevant to transcriptional regulation. These two groups of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 77 publications
1
55
2
1
Order By: Relevance
“…This suggests that the liver lincRNA genes evolved more recently and have not yet dispersed their regulatory regions to more distant genomic loci, as appears to have occurred with regulatory elements of liver-expressed protein-coding genes (111). Based on these findings, we can anticipate that liver-expressed lincRNA and protein-coding gene promoters will be enriched for distinct sets of TF motifs, as was found for human lincRNAs (112). Our finding of high liver lincRNA promoter conservation contrasts with other studies reporting conservation of lincRNA promoters either similar to (4) or lower than (25) those of protein-coding gene promoters in other systems.…”
Section: Discussionmentioning
confidence: 73%
“…This suggests that the liver lincRNA genes evolved more recently and have not yet dispersed their regulatory regions to more distant genomic loci, as appears to have occurred with regulatory elements of liver-expressed protein-coding genes (111). Based on these findings, we can anticipate that liver-expressed lincRNA and protein-coding gene promoters will be enriched for distinct sets of TF motifs, as was found for human lincRNAs (112). Our finding of high liver lincRNA promoter conservation contrasts with other studies reporting conservation of lincRNA promoters either similar to (4) or lower than (25) those of protein-coding gene promoters in other systems.…”
Section: Discussionmentioning
confidence: 73%
“…Whereas in general terms lincRNAs and mRNAs share similar histone marks, such as H3K4me3 in their promoter and H3K36 in the gene body, when comparing expression-matched populations, there are slight differences. Possibly the most striking difference is that H3K9me3-a canonically repressive histone mark-is enriched in the promoters of active lincRNAs (Alam et al 2014) compared to active mRNAs, and that expression of H3K9me3-marked lincRNAs is more tissue-specific than that of lincRNAs lacking H3K9me3. In addition, lincRNAs have fewer transcription factors bound to their promoters than similarly expressed mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies revealed that the expression of lincRNAs is regulated by different types of distal regulatory elements, which is similar to the regulation of protein-coding genes with distal regulatory elements. However, the combinatorial patterns of the chromatin states and the transcription factor binding sites in the promoter regions and distal regulatory elements are distinct between the lincRNAs and protein-coding genes64.…”
Section: Discussionmentioning
confidence: 99%